Flavored Whey Drinks: Preparation and Evaluation of Selected Parameters - Alica Bobková; Martina Fikselová; Tomáš Tóth; Marek Bobko (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of our work was the preparation of fermented flavored whey beverages using whey, probiotic cultures and suitable flavors. Whey fermentation by lactic acid bacteria appears to be an interesting alternative to improve the properties of whey and thus to offer its exceptional nutritional value, not only because of whey protein contained, but also due to the valuable products produced by microorganisms. Pasteurized whey was enriched by the addition of sheep culture ZS-25, which was isolated from sheep cheese and contains more varieties of species Lactococcus lactis, and also by the probiotic culture containing the microorganisms of Bifidobacterium sp., Lactobacillus acidophilus, Streptococcus thermophilus. We focused our attention to select the appropriate type and concentration of flavor as well. Sensory evaluation was performed by the committee consisting of five intentionally selected professionally qualified persons. Taste of fermented whey drink was main observed property. Assessment of prepared whey drinks was repeated four times, each group consisted of 5 samples according to the following structure: sample A - whey drink with culture without flavoring, sample B - whey drink with culture and exotic flavor, sample C - whey drink with the culture and flavor of cranberry-grape-strawberry, sample D - whey drink with the culture and peach-orange flavor, sample E - whey drink with the culture and strawberry flavor. Flavored fermented whey beverages were sensorially evaluated. The order of individual samples determined by the evaluators was statistically processed by the Friedman test. Table value for this test for five evaluators and 5 samples is 8.99. The calculated values for all four sensory evaluations we performed, were higher than 8.99, so we rejected the null hypothesis and proved that among the different flavored whey drinks it is statistically significant difference. Overall, the worst evaluated was whey drink without flavoring. As the best accepted was strawberry flavor, it does not matter whether it was used sheep or cow whey, or sheep culture, ZS-25 or probiotic. We can conclude that strawberry flavor is the most appropriate to cover undesirable taste of whey.